Influência do saque na pontuação de um jogo de voleibol a nível profissional - Bueno Neto, Carlos da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The serve in volleyball is an important foundation within a match. However, the importance it has in the high-level game is little studied. Thus, the objective of this study was to verify the influence of the serve on the result of a match in the main national volleyball league. For this, the service and reception actions of 3 games of the champion team of the Brazilian Men's Volleyball Superliga 2020/2021, EMS Taubaté Funvic, were analyzed. These data were collected from videos made available on the YouTube platform, digitizing them into a volleyball scout spreadsheet. The study consisted of verifying whether the service performed conquered the direct point (Ace - AC), whether it went straight into the net, out or stepped on the line (Wrong Service - SE), whether it managed to hinder the construction of the opponent's attack (Difficult Service - SD), or if there was no difficulty for the opponent's reception (Saque Fácil - SF). The data collected shows that the losing team usually has a high rate of SF and SE, while the winning team usually has a high rate of SD and AC. Thus, it was found that the final score of a high-level volleyball game is highly influenced by the efficiency of the serve's foundation during the match.

O saque no voleibol é um fundamento importante dentro de uma partida. Entretanto, é pouco estudada a importância que ele tem no jogo de alto nível. Dessa forma, o objetivo desse estudo foi verificar a influência do saque no resultado de uma partida da principal liga nacional de vôlei. Para isso, foram analisadas as ações de saque e de recepção de 3 jogos da equipe campeã da Superliga Brasileira de Voleibol Masculino de 2020/2021, EMS Taubaté Funvic. Estes dados foram coletados a partir de vídeos disponibilizados na plataforma do YouTube, digitalizando-os em uma planilha de scout de voleibol. O estudo consistiu em verificar se o saque realizado conquistou o ponto direto (Ace - AC), se foi direto na rede, pra fora ou se pisou na linha (Saque Errado - SE), se conseguiu dificultar a construção do ataque adversário (Saque Difícil - SD), ou se não ofereceu nenhuma dificuldade para a recepção adversária (Saque Fácil - SF). Os dados coletados mostram que a equipe perdedora geralmente possui um alto índice de SF e SE, enquanto que a equipe vencedora geralmente apresenta um alto índice de SD e AC. Com isso, constatou-se que o placar final de um jogo de voleibol de alto nível é altamente influenciado pela eficiência do fundamento do saque durante a partida.
Influence of the service on the scoring of a professional volleyball game
Keywords: Volleyball; Fundamentals; Withdraw; Reception; Efficiency; Voleibol; Fundamentos; Saque; Recepção; Eficiência